Dinâmica espaço-temporal da cobertura dos manguezais e seu potencial para o sequestro de co2 na zona costeira do estado do Maranhão - SANTOS, Adriano de Lima (2022)
Mangroves occupy a significant portion of the coastline around the world, with Brazil being the second country in total area of mangroves. In ICMBio's assessment, 80% of the Brazilian mangroves are distributed in the states of Maranhão (36%), Pará (28%) and Amapá (16%), constituting the largest continuous portion of the ecosystem. Vegetated coastal ecosystems are one of the largest carbon sequestrators on the planet, being an important element in mitigating the impacts of global climate change. Studies that quantify these rates will contribute to national and international discussions on the subject. Seeking to analyze the spatial-temporal dynamics of mangrove cover and its potential for carbon sequestration in the Coastal Zone of the State of Maranhão, this research was applied to the entire coastal zone of Maranhão. All the matrix data came from the MAPBIOMAS project and its data was classified according to its stage of succession, based on the age recorded for each pixel. We considered mangroves in primary stage of succession, all the cover detected for the beginning of the time series and all new areas recorded from the following year were considered as secondary stage. The carbon accumulation model to estimate CO2 stock, sequestration, emission and emission balance was assigned based on the extent of mangrove gains and losses by age. The primary mangroves in 2020 totaled 459,998.09 ha, which, with about 94% of all carbon stock, this region comprises about 1,113.20 ± 522.57 Tg CO2. And, with a total area of 82,893.58 ha, the secondary mangroves stored a total of 78.35 ± 35.98 Tg CO2. The more detailed evaluation allowed a better understanding of the dynamics of area gain, where a decreasing pattern in effective area gain capacity and emission balance was observed, and there was a clear downward trend in their values.